PELATIHAN DAN PEMANFAATAN MEDIA SOSIAL UNTUK MENINGKATKAN PEMASARAN PRODUK PADA MASA PANDEMI COVID-19 - Anita Sumelvia Dewi; Erwin Syahputra; Aprilia Dian Evasari (Batara Wisnu : Indonesian Journal of Community Services, 2022)
This community service activity was carried out with the participants of the PKK Dusun Cakruk Tales Village, Ngadiluwih District, Kediri Regency which has Micro, Small and Medium Enterprises (MSMEs). Technology that is developing rapidly allows us to continue to communicate and carry out business activities amidst the COVID-19 pandemic. With the existence of social media, of course, it can make it easier, help businesses and develop their marketing strategies.The purpose of this service is to provide training on the use of social media to improve marketing. The problem that occurs with partners is the lack of product marketing for Micro, Small and Medium Enterprises (MSMEs). The solution offered here is to provide education and training related to the use of social media and skills training in taking product photos. The method of activity used in this community service is the method of lecture, question and answer, discussion and practice. The result of this community service is the transfer of partner knowledge to market MSME products through social media and the skills to take photos of their products